CHARACTERISTICS OF SHACKLE GRAPH: Shack(Kn,v(j,i),t), Shack(Sn,v(j,i),t), & Shack(K(n,n),v(rj,i),t) - Firmansyah Firmansyah; Abdul Mujib (AXIOM : Jurnal Pendidikan dan Matematika, 2021)
Abstrak:Operasi schackle adalah operasi antara dua atau lebih graf yang menghasilkan graf baru. Graf shackle dinotasikan adalah graf yang dihasilkan dari t salinan dari graf yang diberi simbol dengan dimana dan t bilangan asli. Operasi shackle ppada penelitian ini adalah shackle titik. Operasi shackle titik dinotasikan dengan artinya graf yang dibangun dari sembarang graf sebanyak salinan dan titik sebagai . Kelas graf yang akan di eksporasi karakterisinya dan bilangan kromatinya adalah , S , & S . Hasil penelitiannya menunjukkan bahwa bilangan kromatik graf shackle sama dengan subgraf pembangunnya. Kata Kunci:Operasi Shackle, Shackle titik, graf shackle, bilangan kromatik. Abstract:A shackle operation is an operation between two or more graphs that results in a new graph. Shackle graph notated is a product graph from copy of graph is denoted by where and are natural numbers. The shackle operation in this research is vertex shackle. Vertex shackle operation is denoted by which means that the graph is constructed from any graph as many as copies and vertex as linkage vertex. The class of graphs examined in this study are , S , & S . The results show that the chromatic number of the shackle graph is the same as the subgraph that generates it. Keywords:Shackle Operation, Vertex Shackle, Shackle Graph, Chromatic Numbers.